E-Textbooks as a Teaching Aid at a University of Technology in South Africa: A Cultural-Historical Activity Theory Analysis - Ekaterina Rzyankina (MDPI AG, 2024)
The past two years saw a rapid proliferation of information and communication technologies (ICTs) in higher education. Digital technologies and environments offer many affordances. New digital literacy practices in universities have implications for teaching and learning. E-textbooks, in particular, act as mediating tools that can facilitate teaching and learning through developing students' understandings of scientific concepts. This paper positions e-textbooks as mediators of learning, rather than merely objects of learning. There is thus a need to understand the mediating role of e-textbooks that lecturers draw on in their teaching. While much research was conducted on students' use of e-textbooks, relatively little was conducted on lecturers' use of e-textbooks in engineering education. The current study aimed to answer the following research question: What are lecturers' perspectives on the use of e-textbooks to facilitate learning in engineering? To address this question, data were collected through five individual interviews conducted with engineering lecturers working in the Extended Curriculum Programme (ECP) of first-year students from three engineering departments (chemical engineering, mechanical engineering, and nautical science) at a university of technology in South Africa. The data were analysed using thematic content analysis with the help of ATLAS.ti. Data analysis was guided by a theoretical framework that drew on the cultural-historical activity theory (CHAT). In this study, the focus was on e-textbooks as pedagogical tools within engineering teaching and learning. The findings provide insight into how lecturers incorporate e-textbooks into their teaching, but also reveal the extent to which new digital literacy reading practices remain unfamiliar to engineering lecturers. CHAT enabled the identification of a critical insight, namely, the tension between mediation and division of labour. This highlights important aspects of the discourse surrounding seamless technology integration in higher education. The discussion points to the need for an expansive transformation regarding the use of e-textbooks as important mediating tools for teaching and learning.